Universal tick vaccines: Candidates and remaining challenges - Parizi, L.F.; Githaka, Naftaly W.; Logullo, C.; Zhou, J.; Onuma, M.; Termignoni, C.; Silva Vaz, I. da (MDPI, 2023)
Recent advancements in molecular biology, particularly regarding massively parallel sequencing technologies, have enabled scientists to gain more insight into the physiology of ticks. While there has been progress in identifying tick proteins and the pathways they are involved in, the specificities of tick-host interaction at the molecular level are not yet fully understood. Indeed, the development of effective commercial tick vaccines has been slower than expected. While omics studies have pointed to some potential vaccine immunogens, selecting suitable antigens for a multi-antigenic vaccine is very complex due to the participation of redundant molecules in biological pathways. The expansion of ticks and their pathogens into new territories and exposure to new hosts makes it necessary to evaluate vaccine efficacy in unusual and non-domestic host species. This situation makes ticks and tick-borne diseases an increasing threat to animal and human health globally, demanding an urgent availability of vaccines against multiple tick species and their pathogens. This review discusses the challenges and advancements in the search for universal tick vaccines, including promising new antigen candidates, and indicates future directions in this crucial research field.